(3GdCSFdI GdfaSjI hGdCLhHI GdbOSjIs - (3YHO Gddg Hf EHQGgje Hf MSf Hf eMeO Cejf, CHh GdSjGOI Yaja GdOjf ejQZfj(B: (3Gdecj GdWGFaj GdedbH HGdeMLhH,J (B1207 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPj faS GdfahS GdeWeFfI HfaGFS GdehGgH hGdecGSH hQhM GdCQhGM GdeSJcfI s
(3BNQgG (B:s
(3abO Je fSN GdCSFdI GdeQVjI hGdCLhHI GdSfjI GdYdjI s
(3GdfSNI HgG MhGTs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B4 - (3U (B64 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B6 - (3U (B16s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI s
Keywords: (3GdJUha hGdBOGH GdTQYjIs